2008
DOI: 10.1002/jrs.1903
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the stimulated Raman scattering threshold in droplets on the temporal stretching of a nanosecond laser pulse

Abstract: For linear Raman spectroscopy in micro-droplets the excitation laser energy and therefore the signal strength is limited either by the threshold for the excitation of nonlinear processes in the droplets or by the generation of a plasma (gas breakdown) in the vicinity of the droplets. These processes are due to the enhancement of the excitation field by morphology-dependent resonances (MDRs) which are built up in the cavity synthesised by the droplets. As these stimulated signals disturb the detection of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…With the extinction coefficient known, a complementary measurement (using, for instance, laser-induced fluorescence (LIF) [4,5], Raman scattering [8,9], polarization ratio [10], or elastic scattering at a different wavelength [11]) of either size or number density would directly yield the other quantity. Laser sheet illumination is an attractive technique for twodimensional mapping of volumetric two-phase flows thanks to its small depth of field and large field of view.…”
Section: Introductionmentioning
confidence: 99%
“…With the extinction coefficient known, a complementary measurement (using, for instance, laser-induced fluorescence (LIF) [4,5], Raman scattering [8,9], polarization ratio [10], or elastic scattering at a different wavelength [11]) of either size or number density would directly yield the other quantity. Laser sheet illumination is an attractive technique for twodimensional mapping of volumetric two-phase flows thanks to its small depth of field and large field of view.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the laser beam diameter is expanded to 32 mm by a telescope to decrease the fluence. The details of the pulse stretcher are described elsewhere 28. The λ/2‐plate rotates the polarisation of the laser pulse perpendicular to the scattering plane before it is focused into the measurement chamber by a spherical lens (Ø = 50.8 mm, f = 100 mm).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of droplets can lead to strong stimulated Raman scattering (SRS) signals interfering with the desired signal . Malarski and Leipertz investigated the SRS in dependence on the laser pulse duration and found that shorter pulse helps to suppress the interfering signal. They concluded that sufficiently short pulses cannot be enhanced in the microcavity of a droplet for geometrical reasons.…”
Section: Applications To Gas‐phase and Combustion Systemsmentioning
confidence: 99%